Ethnomathematics in Mathematics Education: An Integrative Literature Review on Strengthening Citizenship within Graduate Profile Dimensions - Himmatul Ulya; Wahyudi; Purwoko Haryadi Santoso (AlphaMath : Journal of Mathematics Education, 2026)
Ethnomathematics has been widely studied in mathematics education, with most research focusing on the exploration of mathematical concepts within cultural practices or the development of culture-based learning innovations. However, limited studies have specifically addressed how ethnomathematics can be systematically aligned with the Strengthening Graduate Profile Dimensions (SGPD), particularly in supporting the citizenship dimension within the current curriculum framework. Based on the researcher's best search, limited literature has addressed the relevance of ethnomathematics to support the SGPD vision. This study employs an integrative literature review (ILR) to analyze 51 peer-reviewed articles published between 1980 and 2022, primarily sourced from the Scopus and Google Scholar databases, to examine the relevance of ethnomathematics to the SGPD curriculum and its practical applications in mathematics education. The analysis is grounded in theoretical perspectives, including multiculturalism, contextual learning, and culture-based pedagogy. This study develops a theoretical framework integrating constructivism, multiculturalism, RME, CTL, CRT, and CC to explain the role of ethnomathematics in supporting SGPD implementation. Within this framework, culture functions as a contextual and pedagogical foundation for strengthening students’ citizenship values. Several examples of specific applications of ethnomathematics discussed in the literature align with the theoretical lens used. It must be acknowledged that there is still room to develop ethnomathematics as an intervention to improve mathematics learning in the establishment of Student Graduate Profiles.